2014
DOI: 10.3357/asem.3783.2014
|View full text |Cite
|
Sign up to set email alerts
|

Postural Control and Shoulder Steadiness in F-16 Pilots: A Randomized Controlled Study

Abstract: Impaired postural control and steadiness may only be quantifiable in individuals experiencing acute neck pain of certain intensity, and there may be a ceiling effect in the ability to improve these parameters. For individuals with highly developed physiological capacity, a battery of tests with more stringent demands should be considered, e.g., increased number of repetitions, prolonged duration of the tests, or testing with eyes closed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Next, the full texts of 22 selected studies were reviewed. Seven studies were eliminated at this stage, and 15 studies were eligible for quantitative synthesis (Hämäläinen et al, 1993;Newman, 1997;Albano and Stanford, 1998;Jones et al, 2000;Alricsson et al, 2004;Burnett et al, 2005;De Loose et al, 2008;Ang et al, 2009;Lange et al, 2013;Salmon et al, 2013;Lange et al, 2014;Murray et al, 2017;Bahat et al, 2020;Murray et al, 2020;Rausch et al, 2021). The PRISMA flow chart for study selection is presented in Figure 1.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, the full texts of 22 selected studies were reviewed. Seven studies were eliminated at this stage, and 15 studies were eligible for quantitative synthesis (Hämäläinen et al, 1993;Newman, 1997;Albano and Stanford, 1998;Jones et al, 2000;Alricsson et al, 2004;Burnett et al, 2005;De Loose et al, 2008;Ang et al, 2009;Lange et al, 2013;Salmon et al, 2013;Lange et al, 2014;Murray et al, 2017;Bahat et al, 2020;Murray et al, 2020;Rausch et al, 2021). The PRISMA flow chart for study selection is presented in Figure 1.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…Supplementary Figure S1 shows a summary of the risk of bias assessment for RCTs (Alricsson et al, 2004;Burnett et al, 2005;Ang et al, 2009;Lange et al, 2013;Salmon et al, 2013;Lange et al, 2014;Murray et al, 2017;Bahat et al, 2020;Murray et al, 2020;Rausch et al, 2021). All studies were rated as high risk for the term "blinding of participants and personnel" due to the inability to conceal the intervention from the pilots who participated in the training program.…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, available evidence does not allow for an easy comparison of reported SMC outcomes in order to determine whether a particular subsystem is being assessed by each of these tests. 31 Individual studies report different outcomes in different neck pain populations 21,28,32 and source populations. 22,24,27 If groups of tests can be identified that address the different subsystems of CSMC, 4 a test battery could potentially be developed for clinical practice.…”
Section: Introductionmentioning
confidence: 99%